The cytotoxic effect of oxybuprocaine on human corneal epithelial cells by inducing cell cycle arrest and mitochondria-dependent apoptosis. (August 2017) - Fan, W-Y; Wang, D-P; Wen, Q; Fan, T-J
Oxybuprocaine (OBPC) is a widely used topical anesthetic in eye clinic, and prolonged and repeated usage of OBPC might be cytotoxic to the cornea, especially to the outmost corneal epithelium. In this study, we characterized the cytotoxic effect of OBPC on human corneal epithelial (HCEP) cells and investigated its possible cellular and molecular mechanisms using an in vitro model of non-transfected HCEP cells. Our results showed that OBPC at concentrations ranging from 0.025% to 0.4% had a dose- and time-dependent cytotoxicity to HCEP cells. Moreover, OBPC arrested the cells at S phase and induced apoptosis of these cells by inducing plasma membrane permeability, phosphatidylserine externalization, DNA fragmentation, and apoptotic body formation. Furthermore, OBPC could trigger the activation of caspase-2, -3, and -9, downregulate the expression of Bcl-xL, upregulate the expression of Bax along with the cytoplasmic amount of mitochondria-released apoptosis-inducing factor, and disrupt mitochondrial transmembrane potential. Our results suggest that OBPC has a dose- and time-dependent cytotoxicity to HCEP cells by inducing cell cycle arrest and cell apoptosis via a death receptor-mediated mitochondria-dependent proapoptotic pathway, and this novel finding provides new insights into the acute cytotoxicity and its toxic mechanisms of OBPC on HCEP cells.